ASSESING CONTENT VALIDITY ON THE CRITICAL THINKING TEST IN CRITICAL LISTENING CLASS - daniel ari widhiatama; Dangin Dangin (Journal of English Language Teaching and English Linguistics, 2021)
Critical thinking is a skill that should be developed to enable students cope with 21st century challenges. Critical Listening class is one of the compulsory subjects in English Language Education Study Program of Mercu Buana University Yogyakarta which goal is to enhance students critical thinking whenever they listen to particular information. However, the instrument to measure the students’ critical listening skill has not been developed yet. Therefore, this study aims at developing an instrument to develop students’ critical listening skill. The study was started by developing the conceptual definition and operational definition of critical thinking and critical listening. Afterwards, a set of instrument containing of 40 items were developed. Identifying instrument content validity is the first step the focus of this study. The instrument items were then validated by 3 experts. The result of this study showed that 30 items on the instrument was considered valid as they had I-CVI ranged from 0,8-1. The other 10 items were deemed to be invalid since the I-CVI is lower than 0,78. The result of this study encouraged the researcher to revise the instrument and improve the validity of the items.